The Use of Terrain Cure in the Treatment and Rehabilitation of Patients with Cardiovascular Diseases: a Review - Tatiana A Knyazeva; Tatiana I. Nikiforova; Andrey A. Lobanov (Вестник восстановительной медицины, 2022)
INTRODUCTION. The review is devoted to the study of one of the modern complex methods of treatment and rehabilitation of patients with cardiovascular diseases – terrain cure which includes elements of therapeutic physical training, climatotherapy and provides for dosed physical activity in the form of hiking in rough terrain, climbing in mountainous areas on specific, marked routes under the supervision of a doctor. It is a method of exercise therapy that improves endurance, cardiovascular, respiratory and nervous system function, metabolism, as well as the muscles of the limbs and trunk. AIM. To highlight the mechanisms of the complex action of terrain cure, combining elements of climatotherapy and metered physical activity for the most optimal use in patients with pathology of the cardiovascular system, including those with excess body weight. MATERIAL AND METHODS. The analysis of publications in the electronic databases PubMed and the Russian Scientific Citation Index by keywords: terrain cure , metered physical activity, climatotherapy, rehabilitation, cardiovascular diseases. The date of the last search is August 9, 2022. CONCLUSION. The world and domestic scientific and practical experience of the use of terrain cure testifies to its high efficiency and an increase in the adaptive and compensatory potential of the patient's body, the safety of using this method in both preventive and therapeutic and rehabilitation programs, due to the main mechanisms of its rehabilitative action. Taking into account its wide availability, cost-effectiveness and additional therapeutic effects when in contact with the terrain, it seems advisable to expand the introduction of the terrain cure and use it for preventive purposes not only in sanatorium–resort conditions, but also in the urban environment – parks and other recreation areas of citizens.